Revitalisasi PAUD Jannati Guna Meningkatkan Daya Tarik Terhadap Pendidikan Anak Usia Dini - Arifuddin Arifuddin; Taufik Hidayat (LP2M Universitas Muhammadiyah Enrekang, 2023)
The lack of facilities and also the beauty of the Early Childhood Education School building means that many parents are not interested in sending their children to Early Childhood Education. This revitalization activity aims to increase the interest of parents in the importance of Early Childhood Education (PAUD). The method used in this activity uses qualitative methods. Data collection techniques for this service activity were carried out using observation, interviews and implementation processes. This revitalization activity was carried out by decorating the walls of the building in the form of hijaiyah letters, letters of the alphabet and numbers with the aim of education and learning. Based on this activity, it is known that the revitalization of Early Childhood Education Jannati in Selat Baru Village is through the preparation of SOP (Standard Operating Procedures) in order to increase the attractiveness of residents in Selat Baru Village to be able to send their children at an early age to Jannati Early Childhood Education. of course to improve character from an early age.